Short Communication: The growth response of indigenous microalga Synechococcus sp. to different concentrations of a heavy metal Cd - GUNAWAN GUNAWAN; MUHAMAT MUHAMAT (Nusantara Bioscience, 2015)
Abstract. Gunawan, Muhamat. 2015. The growth response of indigenous microalga Synechococcus sp. to different concentrations of a heavy metal Cd. Nusantara Bioscience 7:  177-179. Microalgae are aquatic organisms having the capability of absorbing heavy metals. The objective of this study was to analyze the response of microalga species Synechococcus sp. to different concentrations of a heavy metal Cd and its ability to absorb Cd. The microalga used in this study was isolated from a pond in coal mined land. This experiment was conducted using a completely randomized design with five treatments and three replications. The microalga was grown in one liter of BG 11 medium, with Cd concentrations of 0.56 mg/L, 1 mg/L, 1.8 mg/L, 3.2 mg/L, and 5.6 mg/L. The microalga was grown for 14 days and the growth pattern was analyzed. The heavy metal analysis was done using Inductively Coupled Plasma. The numbers of microalga cells after 14 days of culture were 1.015 cell/mL, 866 cell/mL, 800 cell/mL,768.50 cell/mL, and (440 cell/mL) at Cd concentrations of 0.56 mg/L, 1 mg/L, 1.8 mg/L, 3.2 mg/L, and 5.6 mg/L respectively. The concentrations of heavy metal in the medium at the end of experiment were 0.350 mg/L, 0.615 mg/L, 0.471 mg/L, 0.828 mg/L, and 1.456 mg/L, respectively declining from the initial concentrations of 0.56 mg/L, 1 mg/L, 1.8 mg/L, 3.2 mg/L, and 5.6 mg/L. The decline of Cd concentration in the medium at the end of experiment showed that Synechococcus sp. had the capability of absorbing heavy metals from its environment.